The limits of internet self-regulation – the EU’s policy for digital internet intermediaries - Simpson, Seamus (Frontiers in Communication, 2024)
This article contributes to knowledge on EU policy for Internet intermediaries by providing a characterisation and analysis of the system of governance for intermediaries set out initially in the 2000 Directive on E-Commerce and recently updated in the 2022 Digital Services Act. The article shows how the new regulatory system of the DSA, unlike its predecessor, is underpinned by a strong European public transnational network governance approach, with a very noteworthy instantiation of regulatory responsibility at the EU level in respect of the power given to the European Commission to regulate Very Large Online Platforms (VLOPs) and Very Large Online Search Engines (VLOSEs). This reflects an attempt to mitigate the negative consequences of a largely light touch, self-regulated environment faced by Internet intermediaries. The article contends that the EU's new system of platform regulation creates instead a trans-European network (public regulatory dominated and epistemic regulatory actor enabled) more akin to the neoliberal model of EU telecommunications governance than the private interest self-regulatory aspirations of Internet governance specialists of the early 2000s, when the DEC was established.